IDENTIFIKASI DINI PADA SISWA KELAS II DAN III DENGAN GANGGUAN BELAJAR SPESIFIK DISLEKSIA DI SEKOLAH DASAR - Ajeng Raraningrum; Mursidah Rahmah; Riksa Suci Imaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the process, learning carried out by students does not always run smoothly. There are various factors that influence the student learning process, one of which is the specific learning difficulty of dyslexia. Dyslexia is a condition of learning difficulties in children which focuses on the child's reading ability and affects writing and numeracy skills. Measurements were carried out using a special dyslexia instrument sourced from the Guide to Classification and Diagnosis of Mental Disorders (PPDGJ-III) andDiagnostic and Statistical Manual of Mental Disorder (DSM-V). Early identification focuses on measuring the linguistic, cognitive, psychological, sensori-motor and biological/hereditary abilities of dyslexic subjects. The aim of this research is to identify early symptoms of dyslexia in students in grades II and III of elementary school using an early dyslexia identification instrument. This research uses a case study method with a single case study research design. In this study there were 13 subjects with 4 subjects having the highest probability of suffering from dyslexia based on tests on subjects with the early identification of dyslexia instrument. One of the factors to consider when determining dyslexia cannot be separated from public health conditions. Heredity and biology are one of the biggest factors to be taken into consideration, considering that the heredity factor is inherited by the father's genetics by 46% and by the mother by 33%.